Effects of Antiepileptics on Lateral Geniculate Nucleus-Kindled Seizures in Rats - Takashi Ishikawa; Akinori Fujiwara; Kenshi Takechi; Chiaki Kamei (Elsevier, 2009)
The present study was undertaken to clarify the characteristics of lateral geniculate nucleus (LGN) kindling in rats, especially the efficacies of antiepileptics, in comparison with those of amygdala (AMG) kindling. Daily electrical stimulation of the LGN led to the development of a generalized convulsion (kangaroo posture and falling back) in all subjects, similar to AMG kindling. The kindling response of the LGN differed from that of the AMG in a number of respects, that is, a high after-discharge (AD) threshold, a large number of stimulations for completion of kindling, and a different pattern of electroencephalogram (EEG) development. On the other hand, the oral administration of sodium valproate, carbamazepine, clobazam, or zonisamide caused dose-dependent inhibitions of both seizure stage and AD duration of LGN-kindled seizures, whereas ethosuximide had no significant effects. In addition, seizure stage was more potently inhibited than AD duration by these antiepileptics, particularly with clobazam. In conclusion, LGN kindling possesses characteristics that are different from AMG kindling. In addition, it was demonstrated that LGN kindling is a useful model, similar to other types of limbic system kindling, for the evaluation of antiepileptics. Keywords:: lateral geniculate nucleus, amygdala, kindling, antiepileptic